Commission of the Crime of Theft by Unknown Persons - Sharipov Asror Safar ugli (Genius Journals, 2024)
The socio—economic changes that significantly changed the political course of Russia I the late XX - early XXI centuries caused instability of the state economy and an increase in crime,especially theft of other people's property
Keywords: Crime; Russian crime structure